QUAY CONTAINER CRANE PRODUCTIVITY EFFECTIVENESS ANALYSIS (CASE STUDY JAKARTA INTERNATIONAL CONTAINER TERMINAL) - Imam Pekih, Mufti; Sutawijaya, Ahmad Hidayat (International Journal of Mechanical Engineering Technologies and Applications, 2023)
The purpose of this study is to determine the effectiveness and productivity of Quay Container Crane (QCC) work through the value of OEE (availability, performance, quality) and identify losses affecting the OEE value of QCC. The method used is a explorative and descriptive analysis, which exposes availability, performance and quality of Quay Container Crane based on actual data and information by collecting, compiling, classifying and analysing data and information about the effectiveness and productivity of Quay Container Crane. The results of the OEE are analysed using the six big losses method to find the loss factor, root cause analysis using the Fishbone diagram and make improvement recommendations using the 5 why analysis method. Based on the research results, the OEE value of Quay Container Crane affected by the loss factor which are reduce speed losses, breakdown losses and idling and stoppage losses. The root of the problem comes from various causes, among others, many breakdown on spreaders, the maintenance schedule is still not correct, the operator's competence and knowledge are still lacking, and the technical problems in the Quay Container Cranes.